2021
DOI: 10.1021/acsbiomaterials.0c01659
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Hydrothermal Synthesis of Novel 3D Hybrid Nanostructures on Titanium Surface with Mechano-bactericidal Performance

Abstract: Titanium is extensively employed in modern medicines as orthopedic and dental implants, but implant failures frequently occur because of bacterial infections. Herein, three types of 3D nanostructured titanium surfaces with nanowire clusters (NWC), nanowire/sheet clusters (NW/SC) and nanosheet clusters (NSC), were fabricated using the low-temperature hydrothermal synthesis under normal pressure, and assessed for the sterilization against two common human pathogens. The results show that the NWC and NSC surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 74 publications
(152 reference statements)
1
25
0
Order By: Relevance
“…In general, the nanostructure had certain antibacterial performance, but the overall antibacterial activity was indeed relatively poor. 48,49 In spite of these, at the same time, some research studies had demonstrated that the nanostructure had other meaningful benefits. Wang et al 50 displayed that the nanorod array structure could effectively reduce the initial adhesion of bacteria and increase the adhesion of mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the nanostructure had certain antibacterial performance, but the overall antibacterial activity was indeed relatively poor. 48,49 In spite of these, at the same time, some research studies had demonstrated that the nanostructure had other meaningful benefits. Wang et al 50 displayed that the nanorod array structure could effectively reduce the initial adhesion of bacteria and increase the adhesion of mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…aureus, suggesting that the bactericidal activity of the nanostructured Ti surface was low. In general, the nanostructure had certain antibacterial performance, but the overall antibacterial activity was indeed relatively poor. , In spite of these, at the same time, some research studies had demonstrated that the nanostructure had other meaningful benefits. Wang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the natural surfaces with bactericidal nanostructures such as cicada wings, a large number of biomimetic nanostructures with bactericidal performance have been designed on the surface of various materials. For instance, many kinds of bactericidal nanostructures have been extensively built on the surfaces of titanium-based materials to solve the problem of implant failure due to the relevant bacterial infections. ,, In order to further construct the more efficient physical sterilization surface and expand its applications in the fields of medical hygiene, environmental protection, and so forth, it is necessary to clarify the interaction between nanostructures and bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to kill bacteria, a surface should damage the bacterial membrane using the nanostructure [25][26][27]. Meanwhile, several studies have reported mechanically induced bactericidal activity on implanted metallic devices [25,[28][29][30]. However, there are very few studies of nanofabrication based on PCL, and the reported studies do not focus on the antibacterial effects but on cell proliferation and differentiation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%